Pre-Emptive Analgesic Effect of Tramadol and Ibuprofen After Impacted Mandibular Third Molar Extraction - Bara S. Minwah (University of Mosul, College of Dentistry, 2017)
Aims: to evaluate the efficacy of analgesia produced by preoperative administration of tramadol or ibuprofen on surgically extracted mandibular 3rd molars .Materials and Methods :surgical removal of lower 3rd molar was performed in 30 patients , they were divided into three groups of ten patient for each. Group I: preoperative 100mg tramadol IM injection; Group II: preoperative 800 mg Ibuprofen orally; Group III: control group with no preoperative treatment .Analgesia was assessed by visual analogue scale (VAS), Verbal pain Scale(VPS), patient satisfaction(PS), amount of analgesic consumption and time elapsed before first intake were recorded after 24 hours. Results: There was significant differences between tramadol and control group in all types of pain scales in favor of tramadol group . There was significant difference in the visual analog scale (VAS) ,number and time of tablets needed during 24 hours between Ibuprofen and control group . There was significant difference between Tramadol and Ibuprofen groups in both of (VAS) and (VPS) in favor of Tramadol group. Conclusions: The use of tramadol or ibuprofen preemptively is effective method of postoperative pain control in impacted lower 3rd molar surgery .